Assessing the Knowledge and Practice of E-Tracker Among Nurses in the Ho Municipality - Azumah, John Yao; Takramah, Wisdom Kwami; Aheto, Justice Moses K (Journal of Health Informatics in Africa, 2022)
Background and Purpose: Electronic health is an integration of technology in healthcare delivery to facilitate its service delivery. It ranges from the use of desktops to handheld devices to facilitate care, data capture, and data transmission. Due to the wide ranges of technology usage in varieties of services, the healthcare industry is not left behind. It improves upon quality of data generations to facilitate proper decision making. The current study aimed at evaluating the knowledge and practice of e-tracker among nurses in the Ho Municipality of the Volta region of Ghana. Methods: A descriptive cross-sectional approach was used. Simple Random Sampling technique was used to recruit the participants and a semi-structured questionnaire was used to capture the desired data. Data collected was entered using EpiData 3.0 and further exported into Stata 16 IC for analysis. Results were presented using tables and graphs. Results: 129 (69.3%) of the nurses had high knowledge of e-tracker while 42 (22.6%) had high e-tracker usability. 66 (35.5%) of nurses synchronized data immediately after entry while 114 (61.3%) do not ask clients whether if they had been enrolled onto the e-tracker for their first visit. Nurses who consulted District (HI) were 4.9 [COR=4.9; CI(95%)=2.45 – 9.63; p-value=0.000] and 6.8 [AOR=6.8; CI(95%)=2.78 – 16.53; p-value=0.000] times to have high knowledge than their counterparts that did consult their in-charges for assistance. Conclusions: Though there was a high knowledge level of e-tracker among nurses in the Ho municipality there was a very low usability of e-tracker among nurses.